The Principle Implementation of Innocence Presumption by Concluding Pretrial Cooperation Agreement - A. A. Suvorova; Y. E. Kaygarodova (Сибирское юридическое обозрение, 2014)
The article is devoted to some peculiarities of implementation of separate provisions of innocence presumption principle by the conclusion of the pre-trial cooperation agreement.